Complex distal pancreatectomy outcomes performed at a single institution. (September 2018) - Gough, Benjamin L.; Levi, Shoshana; Sabesan, Arvind; Abdel-Misih, Raafat; Bennett, Joseph J.
Abstract: Objective: Discuss the outcomes of distal pancreatectomy in a high volume academic community cancer center. Introduction: Distal pancreatectomy can be done with minimal morbidity and mortality in high volume centers. However, there are limited reports of distal pancreatectomy being performed in the community. This study sought to define the experience with distal pancreatectomy at a high volume community cancer center with a dedicated surgical oncology team. Methods: A retrospective chart review was performed for patients undergoing distal pancreatectomy performed over a twelve year period (2005–2017) at an academic community cancer center. Results: 157 patients underwent distal pancreatectomy. The distribution of open, laparoscopic and robotic resections were 96 (61%), 42 (27%) and 19 (12%) respectively. Concomitant organ resection other than splenectomy was performed in 54 (34%) patients. Spleen sparing resections were performed in 6 (4%) patients. 84 (54%) out of the 157 resections had a malignant lesion on final pathology. Median length of stay was 6 days with 25 (16%) patients readmitted within 30 days. Grade 3 or 4 morbidity rate was 18% (28/157). The incidence of clinically significant pancreatic fistula (Grade B/C) was 8% (13/157). The reoperative rate was 3% (5/157). Overall 30 day mortality in all patients was 0.6% (1/157). Conclusion: This is the largest series of distal pancreatic resections reported in a community cancer hospital. In a high volume academic community cancer center with a dedicated surgical oncology team, distal pancreatic resections can be performed with short hospital stays, minimal morbidity, and a mortality rate of less than 1%. Highlights: Distal pancreatectomies can be performed in community cancer centers with excellent outcomes. Surgical volume is a shortsighted metric to evaluate institutional outcomes. Regionalization of pancreatic surgery is fraught with unintended consequences.